ANALISIS STRUKTUR DAN NILAI-NILAI PENDIDIKAN CERITA RAKYAT “LEBUNG PENDAM” - Hidayati, Anisa; Syafitri, Syarifah; Sirait, Lidia Thimora; Nurrahmah, Silva; Hasanah, Puji Isratul; Lita; Maria, Fanny Lusce; Masykur, Muhammad; Sembiring, Armanta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Culture manifests in various forms, including folktale. This study aims to describe the content, structure, and educational values of the Batanghari folktale titled “Lebung Pendam.” The methodology employed is descriptive qualitative, utilizing historical methods and an objective approach. Data collection was conducted through interviews, literature studies, and document analysis. The findings of this study are: 1) an analysis of the content of “Lebung Pendam,” 2) the structure of “Lebung Pendam,” and 3) the educational values contained within the story. The study results indicate that “Lebung Pendam” belongs to the legend category, narrating the origin of the village of Lopak Aur. There are two versions of the story, differing in the main character's name, the cause of the conflict, and the identity of the character who survives at the end. The intrinsic elements of the story include a linear plot with the theme of social conflict, a rural setting, complex characters, and a moral message emphasizing the importance of thinking before acting and controlling emotions. The educational values identified in the story include morality, social, and religious values.